Divergent thinking and its dimensions: What we talk about and what we evaluate? - Ferrándiz García, Carmen; Ferrando, Mercedes; Soto, Gloria; Sainz, Marta; Prieto, María Dolores (Anales de Psicología / Annals of Psychology, 2016)
This paper examines the role of latent cognitive process and the contents of task (verbal and figural) in divergent thinking. The sample was composed of 260 students, attending different public and semi-public schools in the Murcia Region (Spain), with ages ranging from 8 to 15 years old. Creativity was assessed with the Torrance Test of Creativity Thinking (TTCT) and the Test of Creative Imagination (PIC). Results suggest that, even though both tests are based on the psychometric approach and Guilford´s theory of creativity, their scores are not significantly correlated. Results from confirmatory factor analysis suggest two independent factors (one for each test), more related to tasks’ demands and contents than with the cognitive processes traditionally considered in the definition and measurement of creativity.